Activation of anti-oxidant of curcumin pyrazole derivatives through preservation of mitochondria function and Nrf2 signaling pathway. (May 2019) - Liao, Liping; Shi, Jinguo; Jiang, Caibao; Zhang, Liantao; Feng, Lisi; Liu, Jiayong; Zhang, Jingxia
Abstract: Oxidative stress is an important cause of neurodegenerative diseases. Antioxidant is an potential important method to treat such diseases. The aim of this study is to discover new and effective antioxidants and their mechanism. The neuroprotective effect of six curcumin pyrozole compounds were first evaluated on sodium nitroprusside (SNP) - induced PC12 cell injury by testing cell viability and LDH release. The results showed that four compounds (C1-C4) have more significant protective effects compared to curcumin and edaravone. Furthermore, compounds C1-C4 can attenuate the intracellular ROS, and compound C3 is the most effective one which can preservate the mitochondria function by inhibiting the mitochondrial membrane potential loss and enhance nuclear translocation of Nrf2 in PC12 cell. These results indicated that C3 may be a potential candidate drug for treating neurodegenerative diseases. Highlights: Curcumin pyrazole derivatives C1-C4 can alleviate oxidative stress-induced PC12 neuronal damage. C1-C4 can effectively reduce intracellular ROS, and C3 is the most effective. The protective effect of C3 is related to the protection of mitochondrial function. The protective effect of C3 is related to activation of Nrf2 signaling pathway. C3 may be a potential candidate compound for neuroprotectants in the future.